Penerapan Pembelajaran Iqra’ pada Anak Berkebutuhan Khusus Studi Kasus di SLBN 2 Palangka Raya - Wahyudi Wahyudi; Hamdanah Hamdanah; Saiful Lutfi (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
Religious education, especially the learning of the Qur'an, is one of the most important elements. The Qur'an as a guide to life and a source of knowledge, as the first means or tool of learning that needs to be understood and read. So, it is necessary to learn smoothly. Teaching the Qur'an to children with special needs, especially the disabled, is certainly adjusted and cannot be equated with teaching the Qur'an to other normal children because they have limitations in reading the Qur'an. This study aims to describe how the process or form of learning Iqra' is applied practically to students, to form students to be more accustomed to memorizing, mentioning and knowing the recitations of the Qur'an, as well as identifying various obstacles faced during the process and solutions used by educators to overcome them. This study applies a qualitative approach with the type of case study, where data is obtained through observation, interview, and documentation techniques. The results of the study show that, (1) the learning process or application of Iqra' includes setting goals, such as ensuring that students can read the Qur'an correctly pronounced, memorize hijaiyah letters, and memorize daily prayers. Determine the content of the learning material, which in this case includes learning using the Iqra' book which is compiled into several volumes. The teacher determines the strategies and methods used in Iqra' learning as well as the assessment of reading ability by evaluation. (2) Knowing the obstacles and their solutions, including internal and external factors.